Efficacy of Doxylamine and Pyridoxine during Pregnancy Induced Nausea and Vomiting (Medicine Today, 2024)
Introduction: Nausea and vomiting in pregnancy (NVP) is the most common medical condition of pregnancy causes a significant clinical, psychological and economic burden. Therefore, it is very important to treat this condition appropriately and effectively. The combination of Doxylamine and Pyridoxine is recommended as first-line therapy for nausea and vomiting in pregnancy. Objectives: To observe the therapeutic efficacy of combined Doxylamine and Pyridoxine for treatment of nausea and vomiting in pregnancy. Materials and Methods: An observational study was conducted on patients with nausea and vomiting in pregnancy attended the Model Family planning clinic in the Department of Obstetrics and Gynaecology, Sylhet MAG Osmani Medical College Hospital, Sylhet during the period from January 2019 to December 2019. A total 90 patients with clinically meaningful nausea vomiting (Pregnancy-Unique Quantification of Emesis [PUQE] score > 6) were selected and given 2-4 tablets each containing combined Doxylamine succinate 10 mg and Pyridoxine hydrochloride 10 mg based on a pre-specified titration protocol response to symptoms by respective physician and PUQE score was recorded in all participants before initiation of treatment and at 8th day and 15th day of treatment. In course of follow up period 7 patients were dropped out and finally 83 patients were analyzed in this study. Result: The mean PUQE score was decreased from 10.27 ± 1.76 to 7.94 ± 1.75 at 8th day and to 5.35 ± 1.47 at 15th day of treatment was significant (p